Acute anxiolytic effects of cocaine: the role of test latency and activity phase. - Müller, C; Carey, R; Wilkisz, M; Schwenzner, S; Jocham, G; Huston, J; De Souza Silva, MA (2008)
The emotional effects of the initial consumption of cocaine can have a strong influence on the subsequent use of this drug. Several studies in rodents using long test latencies have reported anxiogenic effects of cocaine. Anxiogenesis, however, would seem to contradict cocaine's well known rewarding effects and its abuse liability. The present study was set up to shed light on conditions that influence cocaine's consequences, namely the time after administration and active vs. resting test phase. The aim of the first experiment was to investigate the effects of cocaine (0, 5, 10, 15 mg/kg, i.p.) on anxiety-related behavior in rats in their active phase with a short test latency of 10 min. In the open field test cocaine had an anxiolytic-like effect, which was confirmed in the elevated plus-maze test. A second experiment investigated the effects of cocaine after a latency of 30 min in animals in their active vs. resting phase. After 30 min significant anxiolytic-like effects were no longer observed in either of the paradigms, irrespective of the activity phase. This and other studies suggest that after first exposure cocaine has acute anxiolytic effects, which rapidly decline, and, may eventually reverse to a longer lasting anxiogenic state.